Православие в Балтии № 5 (14) - (:unkn) unknown (LU Filozofijas un socioloģijas institūts, 2016)
Žurnāla "Православие в Балтии" [Pareizticība Baltijā] Nr.5.(14) struktūru veido trīs nodaļas: zinātniskie raksti, memuāri un dokumentu publikācijas. Pirmajā nodaļā publicētie raksti ir veltīti grieķu katoļu draudžu likvidēšanai Polijas teritorijā 19.gs.otrajā pusē, pareizticīgo dievnamu arhitekta Vladimira Lunska (1862 - 1920) darbībai, reliģiskajām tēmām mākslinieka Jevgenija Kļimova radošajā biogrāfijā, Igaunijas pareizticīgo garīdznieka Aleksandra Kiseļova misijas darba pieredzei, igauņu pareizticīgo bīskapa Romāna (Tanga) dzīves ceļam, kā arī pareizticīgo garīdznieku likteņiem bijušajās Igaunijas teritorijās pēc Otrā pasaules kara. Otrajā nodaļā ir publicētas jurista Borisa Grunduļa (1889 - 1969) atmiņas par dievkalpojuma dziedāšanas praksi. Trešajā nodaļā ir publicēts pārskats par situāciju Rīgas eparhijā 1917. gadā un vēstule par Vormsi salas zviedru pāriešanu pareizticībā (1886).

5th issue of journal “The Orthodoxy in the Baltics” contains three sections: 1. Scientific articles; 2. Memoirs; 3. Publication of documents.An article of Polish historian, Professor Anthony Mironovich “Liquidation of the Commonwealth on the territories of the Polish Kingdom” traces the process of the destruction of the last stronghold of the Uniate Church in the Russian Empire – Greek-Catholic parishes on the territory of the former Kingdom of Poland.An article of the architectural historian, Archpriest Alexander Bertash is devoted to the work of Vladimir Lunskiy – the provincial architect of Livonia and the diocesan architect of Riga at the end of XIX – beginning of the XX century. Anatoly Kinstler in the article “Good Samaritan f. Alexander Kiselev: Experience of work with Russian youth” analyzes the wealthy experience of the missionary activity of the Estonian f. Alexander Kiselev. An article of the son of the artist Yevgeny Klimov – professor of Russian literature Alexei Klimov – is devoted to a little-known page of the artist's work, that is, of his attitude to religion, his attempts to paint icons and to work on mosaics on religious subjects.The material of the St. Petersburg historian Ivan Petrov analyzes the situation of the Orthodox clergy in the former Estonian lands, included after the Second World War in the Russian Federation. Finally, the Estonian researcher Sergey Männik introduces the reader to one of the Orthodox bishops – Estonians – Roman (Tang) biography. In the second section of the periodical, the memoirs of lawyer Boris Grunduls (1889-1969) “On stage and in the choir. Memories of a chorister” are published. In the third section of the periodical, the last report on the state of the diocese of Riga for 1917 (publication by Alexander Gavrilin), as well as “A Letter to the Right Reverend Donat, Bishop of Riga and Mitau, about the conversion of Swedish Vormsi to Orthodoxy” (publication by Lyudmila Dubieva) are published.
Keywords: Владимир Лунский / Vladimirs Lunskis; о. Александр Киселев; Евгений Климов; Архиепископ Роман (Танг); Рижская епархия; Православие, Латвийская Православная Церковь; Research Subject Categories::HUMANITIES and RELIGION::Religion/Theology